The Transformation of MDMC Social Piety in Forming Public Spaces in the Middle of the Covid-19 Pandemic in Indonesia: Transformasi Kesalehan Sosial MDMC dalam Pembentukan Ruang Publik di Tengah Pandemi Covid-19 di Indonesia - Sadikin, Sadikin (Universitas Muhammadiyah Sidoarjo, 2021)
This journal aims to find out how the process of transforming social piety to a disaster management center (MDMC) in the reconstruction of public spaces in the midst of the Covid-19 pandemic in Indonesia. So far, research on MDMC has shown more functions in disaster management, mitigation, preparedness, emergency response and post-disaster rehabilitation. In a broader scope, it has neglected the two most important issues, namely the sociological impact and the formation of a democratic public space from the social transformation process. Therefore, further research is needed on the transformation of MDMC's social piety in reconstructing public spaces in the midst of the Covid-19 pandemic in Indonesia. This study uses a descriptive study of the transformation of social piety to MDMC volunteers in reconstructing public spaces in the midst of the Covid-19 pandemic in Indonesia. By using this qualitative research design, researchers can identify a group of people; study them at home or at work; and develop a general picture of the group, noting how they behave, think and speak. Within the epistemic framework, this study considers several theoretical perspectives on the Covid-19 problem in Indonesia, which has paralyzed the public space, such as grounding the humanitarian movement, caring for Islamic values ​​socially, solidarity in helping and caring for people who suffer from misfortune without expecting it. compensation, giving something to victims who are hit by the disaster based on collective awareness, helping victims who are physically hit by the disaster to reduce the ongoing burden, providing material assistance to victims who are hit by the disaster based on their needs and cooperating in post-disaster rehabilitation.